Deregulation of HDAC1 by p25/Cdk5 in neurotoxicity - Kim, Dohoon (2008)
Aberrant cell cycle activity and DNA damage are emerging as important pathological components in various neurodegenerative conditions. However, their underlying mechanisms are poorly understood. Here, we show that deregulation of HDAC1 activity by p25/Cdk5 induces aberrant cell cycle activity and double-strand DNA breaks leading to neurotoxicity. In a transgenic model for neurodegeneration, p25/Cdk5 activity elicited cell cycle reentry and double-strand DNA breaks that preceded neuronal death. Inhibition of HDAC1 activity by p25/Cdk5 was identified as an underlying mechanism for these events, and HDAC1 gain-of-function provided potent protection against DNA damage and neurotoxicity in cultured neurons and an in vivo model for ischemia. Our findings outline a novel pathological signaling pathway which illustrates the importance of maintaining HDAC1 activity in the adult neuron. This pathway constitutes a molecular link between aberrant cell cycle activity and DNA damage and is a potential target for therapeutics against diseases and conditions involving neuronal death.